Needs of homeless veterans: 5 years of the CHALENG Survey 2012–16. (3rd May 2018) - Tsai, Jack; Blue-Howells, Jessica; Nakashima, John
Abstract: Background: National surveys of homeless veterans have been conducted for over a decade, but there has been no examination of changes in the needs of homeless veterans. Methods: Annual surveys of convenience samples of homeless veterans conducted for Project Community Homelessness Assessment, Local Education and Networking Groups (CHALENG) from 2012 ( n = 6859), 2013 ( n = 7741), 2014 ( n = 7126), 2015 ( n = 3765) and 2016 ( n = 3191) were analyzed. CHALENG surveys collected background information about respondents and their ratings of unmet needs of homeless veterans. Results: Across years, the majority of respondents were males, white, 45–60 years old, Army veterans, lived in urban areas, had no dependent children, and were enrolled in VA healthcare. Over time, the proportion of respondents who were over 60, female, and white increased. There was little change in reported unmet needs with the highest rated unmet needs related to credit counseling, utility assistance, furniture and housewares, dental care and disability income. Among subsamples of veterans with specialized needs, the top three reported unmet needs were housing for registered sex offenders, legal assistance for evictions/foreclosures, and legal assistance for child support. Conclusions: Several intractable unmet needs of homeless veterans have persisted in contemporary time.